Differences in judging judo matches between judges with different qualifications, coaches and players - Kostrzewa, M.; Supinski, J.; Kownacki, S.; Lulinska, E.; Markowski, J.; Pilch, J.; Zak, M.; Marzec, A.; Maszczyk, A. (Physical Activity Review, 2024)
The conducted research aimed to ascertain disparities in the proficiency of appraising combat scenarios among referees varying in their officiating expertise, coaches, and judo athletes. Ninety individuals partook in the study, comprising international referees, national referees, coaches, and judo athletes. Participants were assigned the task of allotting one of six possible ratings to each presented action and categorizing it into one of the groups. A meticulous analysis reveals certain distinctions as well as resemblances in the evaluations of selected actions among referees, coaches, and athletes. A notable incongruity in the appraisal of actions was noted in the shido penalty, where referees demonstrated the most precise assessments, while coaches and athletes rated them similarly. Substantial differences were identified in the evaluation of the hansoku-make penalty, as the coaches' cohort markedly disagreed with the actions depicted in the video and failed to acknowledge that the demonstrated actions warranted the most severe penalty permissible in judo competitions, namely the disqualification of the athlete during the match. Among the three groups examined, referees exhibited the highest level of accuracy in evaluating judo actions. International referees, in comparison to national referees, demonstrated superior assessment of judo actions, and this discrepancy was statistically significant. International referees more effectively evaluated judo actions such as yuko, waza-ari, shido, ippon, and hansoku-make in comparison to union referees. In one instance, union referees exhibited superior assessment of judo actions, specifically in the case of no score actions.